Preparation of PVP-BiOBr Adsorbent for Efficient Indigo Carmine Dye Removal Using Flow-Circulation Systems - Saowapak Teerasong; Thanakrit Saenghirun; Thanawat Sunthornchainukul; Supinya Thammaso; Apiwat Chompoosor; Suwat Nanan (ACS Omega, 2024)
. A flow-circulation system was developed for the treatment of IC dye contaminated water samples. PVP-BiOBr was packed inside a column and did not spill into the water sample after treatment. The removal efficiency was ≥90% after 25 min. The PVP-BiOBr adsorbent could be reused for three cycles. This work demonstrates that PVP-BiOBr is a promising candidate as an adsorbent for IC dye removal. Additionally, the flow-based system establishes an automated operation in continuous mode, which is viable for large scale applications.
Keywords: Adsorption and biosorption for pollutant removal; Nanomaterials for catalytic reactions; Membrane Separation Technologies